AMERICAN UNIVERSITY IN DUBAI, SCHOOL OF ENGINEERING - Alaa K. Ashmawy (Высшее образование в России)
The paper describes School of Engineering of American University in Dubai. The brief historic overview for American University in Dubai and School of Engineering is provided. University’s and School’s organizational and administrative aspects are discussed. The structure of academic programs is discussed as well as their quality assessment. Faculty activities are described in details as well as enrollment requirements. Information about library, laboratory and technology resources is provided. University’s academic and research activities are reviewed in the context of its mission. University community engagement approaches are given.